Beyond the Hidden/Public Resistance Divide: How Bloggers Defeated a Big Company. Issue 9 (September 2017) - Courpasson, David
In recent decades, organizational research on resistance has been largely characterized by a strict divide between hidden and public forms of resistance. We contend that this division impedes a full understanding of how resistance can be efficacious. We suggest that hidden and public forms of resistance are in fact interrelated and mutually reinforced along processes of struggle. In order to study this relationship, we analyze the four-and-a-half-year struggle of a group of dismissed employees against their former employer. This study aims to contribute to the literature in three ways. First, we show that the development of public resistance is nourished by discrete individualistic and non-confrontational expressions of dissent. Second, we demonstrate how the efficacy of resistance is influenced by the meaningfulness of the resisting space constituted by the blog, because of the intricacies between private lives and public roles. Finally, we show that the outcome of resistance is also influenced by the politics of the resisters themselves. We analyze resistance as a dynamic and ambivalent process during which the resisting group can disagree on strategy, thus triggering diverging initiatives that can develop into radicalization.